Association between stressful life events and depression, anxiety, and quality of life among urban adolescents and young adults in Latin America - Diez-Canseco, Francisco; Carbonel, Adriana; Bernabe-Ortiz, Antonio; Olivar, Natividad; Gómez-Restrepo, Carlos; Toyama, Mauricio; Uribe-Restrepo, José Miguel; Brusco, Luis Ignacio; Hidalgo-Padilla, Liliana; Ramirez-Meneses, Daniela; Carbonetti, Fernando Luis; Ariza-Salazar, Karen; et al. (Frontiers in Psychology, 2024)
Background: Latin American youth have a high prevalence of mental health disorders and face major socioeconomic and public safety problems. This study assesses the association between stressful life events (SLEs) and depression, anxiety, and quality of life among adolescents and young adults from deprived neighbourhoods of Latin America.The sample consisted of 2402 participants, between adolescents (15-16 years) and young adults (20-24 years), from Bogotá (Colombia), Buenos Aires (Argentina), and Lima (Peru), assessed in 2021-2022 and recruited in education and community settings and social media. We evaluated the most frequent recent and distant SLEs (occurred in the previous year and more than a year ago, respectively), the relationship between SLEs and severity of depression (PHQ-8), anxiety (GAD-7), and quality of life (MANSA), and we tested for differences by gender and age group.The most common recent and distant SLEs were related to public safety issues and financial distress. Accidents and school suspensions were more frequent among men, and sexual harassment and bullying among women. Every additional reported recent SLE increased the odds of mild, moderate, and severe depression (18%, 17%, and 25%, respectively) and anxiety (10%, 17%, and 21%, respectively) symptoms. Similar trends were found with distant SLEs and depression (8%, 9%, and 11% for mild, moderate, and severe symptoms, respectively) and anxiety (9%, 11%, and 12%, respectively). Furthermore, a higher number of recent and distant SLEs were associated with lower quality of life (β = -.05, p < .001, 95% CI [-0.06, -0.04] and β = -.04, p < .001, 95% CI [-0.05, -0.03], respectively). The relationship between mental distress and quality of life of recent SLEs seems stronger than the one from distant SLEs, and recent SLEs may have a higher impact on adolescents' mental health compared with young adults.Conclusions: Both recent and distant SLEs are related to mental distress and quality of life. Policies and programmes should aim to enhance public and health safety, as well as improve individual, family, and community protective factors that could mitigate the effect of SLEs on Latin American youth.